El acróstico como recurso didáctico para mejorar la producción de textos escritos en los estudiantes del v ciclo del nivel primaria - Viera Medina, Santos (2022)
The present work of professional sufficiency entitled "The acrostic: as a didactic resource to improve the production of written texts in the students of the v cycle of the primary level", aims to improve the production of written texts, the teaching resources are important to improve their abilities of writing, interpretation of texts, how to use the dictionary and its spelling. From the theoretical point of view, the work has its foundation or in the socio-constructivist theory, the constructivist theory and the Haaydes theory exposes the cognitive relationship between the variables such as the production of texts, as well as the positive effects that are had for the process learning derived from its application. With regard to the pedagogical, the strategy is mainly aimed at reinforcing the capacities to adapt the text to the communicative situation, organize and develop ideas in a coherent and cohesive way in children, to achieve the objective we worked during ones applying sessions of learning where group dynamics were included supported with the use of the acrostic. At the end of the pedagogical experience, the results were that when applying the acrostic as a didactic resource, the competence of text production improved, evidenced in the products of the performances shown by the students, we can also observe through the performance diagnostic test that some students they managed to produce acrostics without any difficulty.